2020
DOI: 10.1001/jamainternmed.2019.6958
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Abnormal Exercise Electrocardiography With Normal Stress Echocardiography

Abstract: IMPORTANCE Patients with abnormal (positive) exercise electrocardiography, but normal stress echocardiography (+ECG/−Echo) are commonly encountered in clinical practice; however, the prognostic significance of this discordant result is unclear.OBJECTIVE To determine whether patients with +ECG/−Echo have a higher rate of adverse clinical events and a poorer prognosis than patients with negative exercise ECG and normal stress Echo imaging (−ECG/−Echo).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
19
0
2
Order By: Relevance
“…[1][2][3][4] In the ischaemic cascade, regional wall abnormalities occur before ECG changes. [17] Non-ischaemic stress echocardiograms have been shown to have very low event rates in follow up [1][2][3][4][5][6] including the patients in this cohort (1.2% for all patients at 3 years post testing). As a consequence, patients with ST changes with normal stress imaging have been felt to have a low risk result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In the ischaemic cascade, regional wall abnormalities occur before ECG changes. [17] Non-ischaemic stress echocardiograms have been shown to have very low event rates in follow up [1][2][3][4][5][6] including the patients in this cohort (1.2% for all patients at 3 years post testing). As a consequence, patients with ST changes with normal stress imaging have been felt to have a low risk result.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, one well conducted study has been published suggesting that abnormal exercise ECG findings in the setting of normal stress imaging may result in increased adverse events. [6]…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive testing made a similar prediction of obstructive CAD compared to clinical factors. In addition, a Duke University study of over 15,000 patients found that among patients referred for ICA, those with a positive stress test were less likely to have obstructive CAD compared to those with either a negative stress test or no testing at all [ 19 ]. Recently, the NIH-funded international ISCHEMIA trial demonstrated that in patients with moderate-severe ischemia on functional stress testing, over 14% demonstrated no obstructive CAD on coronary CTA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with discordant or equivocal stress results have an excess risk for adverse cardiac events. In a recent large single-center study, researchers analyzed >15,000 patients undergoing stress testing and found that patients with equivocal stress tests had higher rates of major adverse cardiac events compared to patients with negative stress findings [ 19 ]. Coronary CTA and FFR CT may play an important role in the diagnosis and management of patients with equivocal stress tests.…”
Section: Discussionmentioning
confidence: 99%
“…Women with evidence of ischemia, identified by objective evidence such as abnormal stress or biomarker testing, are more likely to present with no obstructive coronary arteries (INOCA) compared to men, although women report more chest pain. Traditionally, the presence of ischemic ECG changes in the absence of wall motion abnormalities on stress echocardiography is labeled as a “false-positive” stress test, but emerging data indicate that abnormal stress ECG regardless of echocardiographic response should be considered prognostic ( 92 94 ). Additional investigations should be considered to evaluate CMD and vasospasm, as ischemic ECG changes have high specificity for CMD in patients with non-obstructive CAD ( 95 ) and a high prevalence of coronary vasospasm is found in patients with typical exertional angina ( 96 ).…”
Section: Sex/gender In Chest Pain and Ischemic Heart Diseasementioning
confidence: 99%